1984
DOI: 10.4315/0362-028x-47.11.838
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pathogenic Bacteria by Camel's Milk: Relation to Whey Lysozyme and Stage of Lactation

Abstract: Twenty (10%) of 200 milk samples collected from different individual camels inhibited growth of one or more of six pathogenic test organisms in a filter-paper disk assay. The milk samples with inhibitory properties scored zero in the California Mastitis Test. The percentages of milk samples which inhibited Clostridium perfringens, Staphylococcus aureus, Shigella dysenteriae and Salmonella typhimurium were 7.5, 4.0, 2.0 and 1%, respectively. None of the 200 samples inhibited Bacillus cereus or Escherichia coli.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 0 publications
3
40
0
1
Order By: Relevance
“…According to El Hatmi et al, [39] this is due to its richness in soluble proteins which have an antimicrobial effect and to its richness in ascorbic acid which decreases the pH. In fact, the presence of factors limiting bacterial proliferation in raw milk has been demonstrated: high lysozyme content [43] and vitamin C [44]. TAPC count was reach to 2.44×10…”
Section: Milk Compositionmentioning
confidence: 98%
“…According to El Hatmi et al, [39] this is due to its richness in soluble proteins which have an antimicrobial effect and to its richness in ascorbic acid which decreases the pH. In fact, the presence of factors limiting bacterial proliferation in raw milk has been demonstrated: high lysozyme content [43] and vitamin C [44]. TAPC count was reach to 2.44×10…”
Section: Milk Compositionmentioning
confidence: 98%
“…Food Agriculture Organization has reported that more than 18 million camels around the world support the survival of millions of people [14]. Camel milk not only contains more nutrients compared to cow milk [1], but also it has therapeutic and antimicrobial agents [4,12]. Saudi Arabia produced over one percent of world stocks of camels (425,000 head).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have described that the activity of β-galactosidase was independent of the of strain growth rate (Lin et al, 1989;Greenberg et al, 1982). Barbour et al (1984); Gassem and Abu-Tarboush (2000) all showed that dromedary milk failed to reach a gel-like structure (typically of cow milk) after 18 h of incubation due to the presence of growthinhibiting factors.…”
Section: Resultsmentioning
confidence: 99%
“…That was attributed to the presence a variety of protective properties factor against different microorganisms such as lysozyme, lactoferrin; lactoperoxidase and immunoglobulin prevent the growth of lactic acid bacteria. These antimicrobials factors were present in camel milk compared with those in other milk (El-Agamy, 2000;Barbour et al, 1984).…”
Section: Introductionmentioning
confidence: 99%